Optimal Under - voltage Load Shedding using Cuckoo Search with Levy Flight Algorithm for Voltage Stability Improvement - Mwaniki, C; Muriithi, C M.; Abungu, N.O; Nyakoe, G N. (International Journal of Engineering Science Invention, 2015)
Voltage stability has become a serious threat of modern power system operation nowadays. To tackle this problem properly, load shedding is a countermeasure taken as a last resort. However, its consequences might result in huge technical and economic losses. Therefore, this control measure should be optimally and carefully carried out. This paper proposes Cuckoo search with Levy flights (CSwLF) based algorithm for solving the optimal load shedding problem. The amount of load shedding at each bus is determined by applying CSwLF to solve a nonlinear optimization problem formulated in the optimal power flow framework. The performance of the proposed CSwLF based method is tested on the operating conditions of IEEE 14-bus test system.
Keywords: Metaheuristic algorithm; Voltage stability; Cuckoo search; Levy flights; Under voltage load shedding